2019
DOI: 10.1128/jvi.02165-18
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Tetherin Inhibition of Alphavirus Release

Abstract: Tetherin is an interferon-inducible, antiviral host factor that broadly restricts enveloped virus release by tethering budded viral particles to the plasma membrane. In response, many viruses have evolved tetherin antagonists. The human tetherin gene can express two isoforms, long and short, due to alternative translation initiation sites in the N-terminal cytoplasmic tail. The long isoform (L-tetherin) contains 12 extra amino acids in its N terminus, including a dual tyrosine motif (YDYCRV) that is an interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…(iii) One or more antiviral effectors acting during assembly or egress may have roles in this assay, but were missed in the single‐cycle assay of the original screen. Accordingly, we sought to determine whether some of the other previously described anti‐alphavirus effectors contribute to this residual IFN‐mediated restriction of VEEV (Zhang et al , 2007 ; Teng et al , 2012 ; Jones et al , 2013 ; Li et al , 2013 ; Mahauad‐Fernandez et al , 2014 ; Ooi et al , 2015 ; Poddar et al , 2016 ; Weston et al , 2016 ; Weiss et al , 2018 ; Wan et al , 2019 ). We used multiplexed CRISPR‐Cas9 to engineer U‐2 OS cells that have up to four antiviral effectors simultaneously targeted.…”
Section: Resultsmentioning
confidence: 99%
“…(iii) One or more antiviral effectors acting during assembly or egress may have roles in this assay, but were missed in the single‐cycle assay of the original screen. Accordingly, we sought to determine whether some of the other previously described anti‐alphavirus effectors contribute to this residual IFN‐mediated restriction of VEEV (Zhang et al , 2007 ; Teng et al , 2012 ; Jones et al , 2013 ; Li et al , 2013 ; Mahauad‐Fernandez et al , 2014 ; Ooi et al , 2015 ; Poddar et al , 2016 ; Weston et al , 2016 ; Weiss et al , 2018 ; Wan et al , 2019 ). We used multiplexed CRISPR‐Cas9 to engineer U‐2 OS cells that have up to four antiviral effectors simultaneously targeted.…”
Section: Resultsmentioning
confidence: 99%
“…It is also possible that other IFN-induced genes that were not identified by our screens may play a role in restricting VEEV infection. Accordingly, we sought to determine if some of the previously described anti-alphavirus effectors contribute to this residual IFN-mediated restriction of VEEV (Jones et al , 2013; Li et al , 2013; Mahauad-Fernandez et al , 2014; Ooi et al , 2015; Poddar et al , 2016; Teng et al , 2012; Wan et al , 2019; Weiss et al , 2018; Weston et al , 2016; Zhang et al ., 2007). We used multiplexed CRISPR-Cas9 to engineer U-2 OS cells that have up to 4 antiviral effectors simultaneously targeted.…”
Section: Resultsmentioning
confidence: 99%
“…These findings gave rise to hope that nsP1 could be considered as a target for developing tetherin-mediated therapeutics against CHIKV (80). However, a more recent study on the subject could not confirm Jones' report since no evidence for tetherin-antagonists in alphaviruses was found (81).…”
Section: Inhibitors Of Chikv Nsp1mentioning
confidence: 94%
“…Jones ( 80 ) postulated that CHIKV nsP1 is such a BST-2/tetherin antagonist. However, Wan et al ( 81 ) could not confirm Jones' findings and suggested that the sole physical tethering of virus particles to the PM is not sufficient to restrict alphaviruses and that the subsequent virus endocytosis is a requirement for efficient inhibition of alphavirus release.…”
Section: Antivirals Against Chikungunya Virusmentioning
confidence: 94%